Changing conditions of temperature and precipitation in Malda District in the last century: Trends and Characteristics - Naskar, Mousumi (International Journal of Psychosocial Rehabilitation, 2024)
In the context of global warming and human-induced climate change, research on changing weather and climate patterns has gained significant attention. Among various climate parameters, temperature and precipitation are the most important as they directly affect humanity.Many researchers worldwide agree that anthropogenic factors have considerably increased the Earth's temperature over the last century. This study aims to analyze the trends in temperature and precipitation in Malda District, West Bengal, India, over the period from 1901 to 2000. The raw data for the study were obtained from the website www.interwaterportal.com.The research focuses on identifying long-term changes and decadal variations in temperature and precipitation. Additionally, it examines the relationship between temperature and precipitation using linear regression analysis. The study also evaluates the normality of the data to detect any irregular patterns in the distribution of temperature and precipitation, employing the Shapiro-Wilk Test for this purpose.A key finding of the study is that there is no statistically significant pattern in the temporal distribution of temperature and precipitation in the region.